Smith, Susie. Interview about growing up in New Perlican and the goats in the community. - Barrett, Terra (2017)
Terra Barrett of the Heritage Foundation of Newfoundland and Labrador interviews Susie Smith about growing up in New Perlican, children's games, her goat memories, and crafting for The Goats of New Perlican Oral History Roadshow Project in partnership with Heritage New Perlican.